Stop and think parenting - Peterson, Lindy (Hawthorn, Vic. : ACER, 1990)
The parenting road. Attitudes and impulses. Managing children's behaviour. Training children's social skills.
Keywords: Child rearing; Parenting; Social skills in children; Parenting; Child rearing